On-the-job search and the cyclical dynamics of the labor market - Michael U. Krause; Thomas A. Lubik (European Central Bank (ECB), 2007)
We show how on-the-job search and the propagation of shocks to the economy are intricately linked. Rising search by employed workers in a boom amplifies the incentives of firms to post vacancies. In turn, more vacancies increases job search. By keeping job creation costs low for firms, on-the-job search greatly amplifies shocks. In our baseline calibration, this allows the model to generate fluctuations of unemployment, vacancies, and labor productivity whose magnitudes are close to the data, and leads output to be highly autocorrelated.
Keywords: E21; E32; J64; 330; business cycle; job-to-job mobility; propagation; Search and matching; worker flows Beveridge curve; Arbeitsuche; Arbeitsmobilität; Dynamisches Gleichgewicht; Beveridge-Kurve; Konjunktur; Arbeitslosigkeit; Friktionelle Arbeitslosigkeit; Schätzung; USA; Matching